Assessment of Associated Factors with Risk of Relapse in Schizophrenic Patients at Psychiatric Hospitals in Baghdad City - Hasan Hussein, (Iraqi National Journal of Nursing Specialties, 2023)
Schizophrenic patients who are at great risk of relapse are characterized by non-compliance,denial of illness and need for treatment and no contact with family. So, the prevention of relapseand readmission to hospital are crucial in mental health practice.The present study is a descriptive-analytical study that was carried out from November 2nd2006 through the end of 20 of April 2008.Objectives: To assess the associated factors with the risk of relapse in schizophrenic patients atpsychiatric hospitals in Baghdad city.Methodology: A purposive "non-probability" sample of (50) schizophrenic patient who hasdrelapsed was involved in the present study. Data were collected through the use of the constructedquestionnaire and the process of the interview as means for data collection.The questionnaire was constructed by the researcher to achieve the objectives of the study,which consisted of two parts; the first one is concerned with the demographic and clinicalcharacteristics; the second part includes the risk factors of relapse and contains (68) item thatdescribe the factors related to the family support, factors related to the family hardship and factorrelated to the treatment compliance.Data were analyzed through the application of descriptive statistical analysis (frequency,percentage, mean and mean of scores and the relative sufficiency and inferential statistic (MultipleLogistic Regression).Results: The findings of the study indicated that there was a high family support for schizophrenicpatients, high family hardship, moderate level of non-compliance to the treatment and more thanhalf of the patients had (30%) chance of relapse related to the recent exposure to recent life events.